Designing UIs for Static-Analysis Tools: Evaluating tool design guidelines with SWAN. - TIGANOV, DANIIL; QUANG DO, LISA NGUYEN; ALI, KARIM (Communications of the ACM, 2022)
The article examines the application and user interface (UI) design aspects of the Swift computer programming language static-analysis tool known as SWAN. It discusses the effectiveness of the design in order to evaluate future usability by investigating time constraints, analysis responsiveness, and collaboration options.